The Effect Of Laugh Therapy On Decrease Level Of Stress In That Student Develop Scientific Writing - Marwidah; Risnawati (Jurnal Life Birth, 2018)
Scientific Writing is one of the requirements for completion of a student's study and this can cause stress for students, the impact of behaviors that arise include: delaying completion of college assignments, lazy lectures, drug, and alcohol abuse, engaging in activities looking for excessive pleasure and at risk. Stress management that will be given is a strategy to reduce stress levels by applying laughter therapy. Based on interviews conducted on 20 final year students who compiled Scientific Papers at Stikes Panrita Husada Bulukumba students experienced symptoms of stress such as headaches, feelings of tension, anxiety, discomfort, boredom, irritability, irritability, irritability, memory loss, feeling sad, and tend to want to continue to delay work, anxiety, dizziness, decreased appetite, irregular sleep. Objective: a study to find out the effect of laughter therapy on reducing stress levels in students who compile the Scientific Papers of the Diploma III Midwifery Study Program at Stikes Panrita Husada Bulukumba. Research Design: quasi-experiment: pre-test and post-test nonequivalent control group. The population in this study amounted to 96 people and a sample of 48 people who experienced stress in compiling Scientific Papers by taking samples using purposive sampling techniques. Results: research using the Wilcoxon alternative paired T-test shows that the p-value of 0,000 is smaller than the real level (p <0.05). This shows that the posttest data between the experimental and control groups had significant differences, thus the research hypothesis was accepted. Conclusion: the study shows that there is an effect of laughter therapy on reducing stress levels in students who compile the Scientific Papers of Diploma III Midwifery Study Program at Stikes Panrita Husada Bulukumba.